1999
DOI: 10.1111/j.1478-3231.1999.tb00016.x
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of hepatitis C virus (HCV) infection in an HCV epidemic area of Japan: age and sex-related seroprevalence of anti-HCV antibody, frequency of viremia, biochemical abnormality and histological changes

Abstract: We studied the age- and sex-specific prevalence of hepatitis C virus (HCV) infection and aminotransferase abnormalities as well as histological changes in the liver associated with HCV infection. Of the eligible 3,707 inhabitants aged 6 years and older in an HCV infection epidemic area 2,382 (64.3%) were examined. The anti-HCV positivity rate was 20.7% on average and increased according to age. Age was the most potential risk indicator for anti-HCV positivity by multiple stepwise regression analysis. The HCV R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Despite the fact that complications of liver biopsy, although rare, are often serious, liver biopsy is an effective method for evaluating the degree of liver fibrosis, which is essential to determine treatment strategies and the duration of treatment with new direct-acting antiviral agents [Ghany et al, 2009[Ghany et al, , 2011. The proportion of patients who underwent liver biopsy in the Swiss HCV cohort study was 50% [Prasad et al, 2007], whereas it was 49% (range, 33-79%) in a Danish cohort [Christensen et al, 2007], and 69% and 32% in HCV cohorts in Germany and Japan, respectively [Niederau et al, 1998;Kuboki et al, 1999]. In the current study, liver biopsy was performed in 25.7% of the Korean cohort; the rate of biopsy differed significantly according to the attending physician.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that complications of liver biopsy, although rare, are often serious, liver biopsy is an effective method for evaluating the degree of liver fibrosis, which is essential to determine treatment strategies and the duration of treatment with new direct-acting antiviral agents [Ghany et al, 2009[Ghany et al, , 2011. The proportion of patients who underwent liver biopsy in the Swiss HCV cohort study was 50% [Prasad et al, 2007], whereas it was 49% (range, 33-79%) in a Danish cohort [Christensen et al, 2007], and 69% and 32% in HCV cohorts in Germany and Japan, respectively [Niederau et al, 1998;Kuboki et al, 1999]. In the current study, liver biopsy was performed in 25.7% of the Korean cohort; the rate of biopsy differed significantly according to the attending physician.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of patients' medical records, spontaneous elimination of HCV has been reported rarely in some cases of chronic HCV-related disease [Yousuf et al, 1992;Yokosuka et al, 1999;Yoshikawa et al, 2001]. It has been reported that such elimination was found in 6/310 (2%) patients with HCV-related chronic liver disease who were positive for serum HCV RNA; all these cases were in the terminal stage of HCC [Yokosuka et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…In order to elucidate the incidence of spontaneous disappearance of HCV viremia, thereby contributing to our understanding of the natural course of HCV infection, a population-based cohort study is essential. For more than 10 years since 1991, we have carried out an epidemiological study of HCV infection in an area endemic for this disease [Ishibashi et al, 1996;Yoshii et al, 1999;Kuboki et al, 1999]. This populationbased cohort study enabled us to elucidate the incidence of spontaneous elimination of serum HCV RNA in chronically HCV-infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals infected with HCV who are greater than 50 years of age have a more severe disease and higher mortality rate than younger individuals. 14,15 The genetic background of the host as assessed by human leukocyteassociated antigen (HLA) typing has shown some associations with clearance of the HCV during primary infection. [16][17][18][19][20][21][22][23][24] The risk of disease associated with persistent virus infection such as HIV-1, hepatitis B virus, and human T-lymphotropic virus-1 (HTLV-1) is strongly determined by viral load.…”
mentioning
confidence: 99%